2019
DOI: 10.1002/mrm.28097
|View full text |Cite
|
Sign up to set email alerts
|

Prospective GIRF‐based RF phase cycling to reduce eddy current‐induced steady‐state disruption in bSSFP imaging

Abstract: Purpose To propose an explicit Balanced steady‐state free precession (bSSFP) signal model that predicts eddy current‐induced steady‐state disruptions and to provide a prospective, practical, and general eddy current compensation method. Theory and Methods Gradient impulse response functions (GIRF) were used to simulate trajectory‐specific eddy current‐induced phase errors at the end of a repetition block. These phase errors were included in bloch simulations to establish a bSSFP signal model to predict steady‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…All MR-STAT experiments in the current work have been performed with linear, Cartesian sampling strategies. This sampling strategy offers important advantages in the form of robustness to hardware imperfections (e.g., eddy currents, especially for gradient-balanced sequences 43,44 ), less susceptibility to ΔB 0 related blurring artefacts, 45 17 More advanced iterative MRF reconstructions 13,14,48,49 might perform better with Cartesian sampling than the currently used MRF reconstructions (low-rank inversion followed by low-rank dictionary matching), and an in-depth comparison will be the subject of further studies. It should also be noted that neither the MR-STAT framework nor the currently proposed reconstruction algorithm is restricted to Cartesian sampling and further research is also aimed at incorporating non-Cartesian trajectories into MR-STAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All MR-STAT experiments in the current work have been performed with linear, Cartesian sampling strategies. This sampling strategy offers important advantages in the form of robustness to hardware imperfections (e.g., eddy currents, especially for gradient-balanced sequences 43,44 ), less susceptibility to ΔB 0 related blurring artefacts, 45 17 More advanced iterative MRF reconstructions 13,14,48,49 might perform better with Cartesian sampling than the currently used MRF reconstructions (low-rank inversion followed by low-rank dictionary matching), and an in-depth comparison will be the subject of further studies. It should also be noted that neither the MR-STAT framework nor the currently proposed reconstruction algorithm is restricted to Cartesian sampling and further research is also aimed at incorporating non-Cartesian trajectories into MR-STAT.…”
Section: Discussionmentioning
confidence: 99%
“…All MR‐STAT experiments in the current work have been performed with linear, Cartesian sampling strategies. This sampling strategy offers important advantages in the form of robustness to hardware imperfections (e.g., eddy currents, especially for gradient‐balanced sequences), less susceptibility to normalΔB0 related blurring artefacts, and direct availability on clinical MR systems. Within the conventional MRF framework, it is more challenging to work with Cartesian sampling strategies, as demonstrated using the simulation experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging data were acquired using the MRF sequence described by Jiang et al (Jiang et al 2015), which consists of an adiabatic inversion pulse and a sinusoidal flip angle train. One radial line was acquired per time-point (Cloos et al 2016) and subsequent readouts were azimuthally incremented using the tiny golden angle to minimize eddy current effects (Wundrak et al 2015, Bruijnen et al 2019) (Fig. 2).…”
Section: Mrf Pulse Sequence and Reconstruction Methodsmentioning
confidence: 99%
“…It can be observed that the motion-fields are mostly smooth in time, except for small high frequency fluctuations which are mostly visible in end-exhale for both volunteers. These fluctuations may be caused by hardware imperfections [30] or by sensitivity to cardiac motion, which manifest themselves as high frequency fluctuations on top of respiratory motion.…”
Section: ) Online Inference Phasementioning
confidence: 99%